2016
DOI: 10.1016/j.jpeds.2016.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Unsafe Child Feces Disposal is Associated with Environmental Enteropathy and Impaired Growth

Abstract: Unsafe child feces disposal was significantly associated with environmental enteropathy and impaired growth in a pediatric population in rural Bangladesh. Interventions are needed to reduce this high-risk behavior to protect the health of susceptible pediatric populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
59
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 41 publications
(65 reference statements)
7
59
0
Order By: Relevance
“…Our recent work has found significant associations between poor household hygiene practices and elevated faecal markers of EE and impaired growth among young children [6,7,19,28,29]. In our cohort study in rural Bangladesh, we found that animals in the child's sleeping space and poor caregiver hand hygiene were associated with elevated faecal markers of EE [7].…”
Section: Introductionmentioning
confidence: 47%
See 4 more Smart Citations
“…Our recent work has found significant associations between poor household hygiene practices and elevated faecal markers of EE and impaired growth among young children [6,7,19,28,29]. In our cohort study in rural Bangladesh, we found that animals in the child's sleeping space and poor caregiver hand hygiene were associated with elevated faecal markers of EE [7].…”
Section: Introductionmentioning
confidence: 47%
“…The cohort size was based on the number of households that could be recruited between February and April 2014. Our previous work among this cohort in rural Bangladesh found that 84% of households had an unsafe child faeces disposal event during structured observation, 16% had an unimproved sanitation option, 72% had no soap present near the household tubwell during spot checks and 21% of caregivers had hands with visible dirt [7,19].…”
Section: Methodsmentioning
confidence: 84%
See 3 more Smart Citations